SOME DIFFICULTIES OF USING THE MOTHER TONGUE IN THE ENGLISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the challenges associated with the use of the mother tongue (L1) in English as a Foreign Language (EFL) classrooms. While strategic use of L1 can offer benefits such as facilitating comprehension, reducing anxiety, and promoting deeper engagement, its overuse or inappropriate application can impede language acquisition. This paper explores the common difficulties encountered by both teachers and students, including reliance on translation, interference with target language production, and the potential for creating a dependency on L1. Through a review of relevant literature and empirical evidence, this article aims to provide insights into the effective and balanced integration of L1 in EFL instruction, offering practical recommendations for educators seeking to optimize language learning outcomes.